Investigation into mammalian os cordis and cartilago cordis - Best, AS (2022)
This thesis includes a comprehensive literature review of the two major hyperdense tissue types found in the heart: bone and cartilage known as os cordis and cartilago cordis respectively. Alongside this review is an investigation of the cardiac tissue in four mammalian species. The nyala, giraffe, Gorilla and bonobo were all examined using computed microtomography (microCT) and histological techniques. The study included an investigation of 26 hearts across the four mammalian species (nyala n= 1; giraffe n= 1; Gorilla n= 15; bonobo n= 9). The review showed that 13 species had been found with os cordis and 24 species had cartilago cordis present. Having collated all data from these investigations it was possible to observe that os cordis development can occur as a normal anatomical event or, in other species, may form as a direct result of cardiovascular disease. Additionally, how the cartilago cordis forms is yet to fully understood, although is likely to involve neural crest cells. In addition, the formation of os cordis is likely to occur by endochondral ossification (EO) from cartilage, which may more may not, be related to cartilago cordis. Suggested functions of os cordis and cartilago cordis appear to be similar, as a protective structure in areas of high mechanical stress or to aid in contraction. Our own investigations into the nyala, giraffe, Gorilla and bonobo involved X-ray computed microtomography, dissection and histology. The nyala was found to have four ossa cordis, a novel discovery, while the giraffe had one single os cordis. No bone or cartilage were found in the Gorilla or bonobo. Both nyala and giraffe bones showed direct evidence of EO and the presence of os(sa) cordis in both of these species confirmed suggestions that os(sa) cordis occurrence may be linked to genetics since nyala, giraffe and many species with os cordis found in the review originated from the Artiodactyla order. Although neither bone nor cartilage was found in the Gorilla or bonobo hearts, the investigation allowed us to assess fibrosis levels within each heart, a factor which has been shown to directly correlate with os cordis formation.